2018
DOI: 10.1002/ptr.6190
|View full text |Cite
|
Sign up to set email alerts
|

Phyllanthin from Phyllanthus amarus inhibits LPS‐induced proinflammatory responses in U937 macrophages via downregulation of NF‐κB/MAPK/PI3K‐Akt signaling pathways

Abstract: Phyllanthin, a lignan from Phyllanthus species, has been reported to possess potent immunosuppressive properties on immune cells and on adaptive and innate immune responses in animal models. Herein, we investigated the inhibitory effects of phyllanthin isolated from Phyllanthus amarus on nuclear factor-kappa B (NF-κB), mitogen-activated protein kinase (MAPK), and PI3K-Akt signal transducing pathways in LPS-activated U937 cells. The lipopolysaccharide-stimulated excess production of prostaglandin was significan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
24
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 36 publications
(26 citation statements)
references
References 36 publications
1
24
0
1
Order By: Relevance
“…How LPS-induced pathways react is not fully understood. Previous studies have reported that NF-ĸB/MAPK is very important in the MyD88 signaling pathway induced by LPS (26)(27)(28). The NF-ĸB/MAPK signaling pathway plays important roles in inflammatory responses.…”
Section: Expression Of Proteins Of the Lipopolysaccharide (Lps)-myementioning
confidence: 99%
“…How LPS-induced pathways react is not fully understood. Previous studies have reported that NF-ĸB/MAPK is very important in the MyD88 signaling pathway induced by LPS (26)(27)(28). The NF-ĸB/MAPK signaling pathway plays important roles in inflammatory responses.…”
Section: Expression Of Proteins Of the Lipopolysaccharide (Lps)-myementioning
confidence: 99%
“…Akt signal transduction pathway was reported to be responsible for the proinflammatory molecules expression through the NF-κB activation in LPS-triggered cell through numerous studies. 29,30) For that reason, inhibition of the Akt phosphorylation has been identified as a primary key to handle inflammatory diseases. Hence, the stimulation of Akt, possibly correlated with NF-κB activation in LPSstimulated cells, could provide the generation of inflammatory signaling molecules.…”
Section: Discussionmentioning
confidence: 99%
“…The levels of cytokines in LPS-primed cells after treatment with T. crispa extract was investigated by placing 5 × 10 5 cells/mL of differentiated macrophages into 24 well plates supplemented with 4.68 to 75 μg/ mL of T. crispa extract or 0.125 to 2 μg/mL of levamisole (positive control) for 2 h, preceding treatment with LPS (1 μg/mL) for 24 h. DuoSet®ELISA System was employed to analyze the effect of the extract and levamisole on TNF-α and IL-1β synthesis following the manufacturer's directions [11][12][13].…”
Section: Cytokines Immunoassaymentioning
confidence: 99%
“…The extracts were kept at − 70°C until further use. CFX96 Touch Real-Time PCR Detection system, together with SYBR Green RT-PCR Master Mix were utilized for qRT-PCR for mRNA quantification as previously reported [11,12,14].…”
Section: Quantitative Rt-pcr For Determination Of Level Of Relative Gmentioning
confidence: 99%